THE ROLE OF BIOLOGICAL FLUIDS IN THE DEVELOPMENT OF KIDNEY STONE DISEASE - Raxmonov Baxrom Baxtiyor o'g'li (TADQIQOTLAR.UZ, 2024)
Abstract: The role of biological fluids, particularly urine, in the development of kidney  stone  disease  is  paramount  to  understanding  its  pathogenesis.  This  review delves  into  the  dynamics  of  biological  fluids,  including  their  composition, physicochemical  properties,  and  the  balance  of  promoters  and  inhibitors  of crystallization.  It  explores  recent  insights  into  the  influence  of  urine  pH, supersaturation levels, the impact of other bodily fluids, and emerging evidence on extracellular vesicles and the microbiome. The findings underscore the importance of modifying urinary composition through dietary and therapeutic measures to mitigate stone formation risk.